Evaluating the Awareness, Perceptions, and Behaviors Relating to Antibiotic Use and Resistance among Students at Sebha University - Afia Saad Ebraheem; Nadia Salem Alrawaiq; Huda Salem Alrawiq; Nasser alrawiq; Ali. M. Al-Zwi; Shayma’a Almabrouk (African Journal of Advanced Pure and Applied Sciences, 2025)
In Libya, too many antibiotics is a growing problem. This is one of the main reasons why bacteria are becoming resistant to them. We need to teach students more about antibiotic use and resistance. This study looked at how much medical and non-medical students know about antibiotics, what they think about them, and how they use them. At Sebha University, we did a study where we asked people from different fields about their knowledge, attitudes, and practices. 80.0% of the 560 completed and returned questionnaires out of the 700 that were distributed were from medical students. Men made up 18.4% of the respondents, while women made up the majority (81.6%). According to the findings, 58% of the students agreed that taking antibiotic courses was essential, 20% thought that antibiotics could be stopped once improvement was seen, and 22% weren't sure. Of the students, 57.7% agreed, 16.3% disagreed, and 26.1% were not sure that antibiotics speed up recovery from a cold. The statement that "All antibiotics do not cause side effects" was also accepted by 72% of the students. Interestingly, 27.1% of the students compared aspirin and paracetamol (Panadol) with antibiotics. Additionally, only 65.2% of the students acknowledged that antibiotic resistance might pose a serious threat in Libya. Overall, it was found that students' attitudes, knowledge, and practices around antibiotics were mainly lacking, with few positive answers regarding particular practices. This shows that it is very important to teach people about how to use antibiotics properly and the dangers of misusing them.